How dendritic cells sense and respond to viral infections. Issue 19 (14th October 2021) - Marongiu, Laura; Valache, Mihai; Facchini, Fabio A.; Granucci, Francesca
Abstract: The ability of dendritic cells (DCs) to sense viral pathogens and orchestrate a proper immune response makes them one of the key players in antiviral immunity. Different DC subsets have complementing functions during viral infections, some specialize in antigen presentation and cross-presentation and others in the production of cytokines with antiviral activity, such as type I interferons. In this review, we summarize the latest updates concerning the role of DCs in viral infections, with particular focus on the complex interplay between DC subsets and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Despite being initiated by a vast array of immune receptors, DC-mediated antiviral responses often converge towards the same endpoint, that is the production of proinflammatory cytokines and the activation of an adaptive immune response. Nonetheless, the inherent migratory properties of DCs make them a double-edged sword and often viral recognition by DCs results in further viral dissemination. Here we illustrate these various aspects of the antiviral functions of DCs and also provide a brief overview of novel antiviral vaccination strategies based on DCs targeting.